2009
DOI: 10.1021/bc9000596
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Congener Approach to the Design of Ligands for G Protein-Coupled Receptors (GPCRs)

Abstract: Functionalized congeners, in which a chemically functionalized chain is incorporated at an insensitive site on a pharmacophore, have been designed from the agonist and antagonist ligands of various G protein-coupled receptors (GPCRs). These chain extensions enable a conjugation strategy for detecting and characterizing GPCR structure and function and pharmacological modulation. The focus in many studies of functionalized congeners has been on two families of GPCRs: those responding to extracellular purines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 122 publications
2
82
0
Order By: Relevance
“…Compounds 10 , 14 , 19 , and 26 were designed as potential affinity labels of the A 3 AR, but the chemical irreversibility of binding was not tested in the present study. The use of isothiocyanates, 3-isothiazolones, and other electrophilic derivatives to affinity label biopolymers has been described 13,35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 10 , 14 , 19 , and 26 were designed as potential affinity labels of the A 3 AR, but the chemical irreversibility of binding was not tested in the present study. The use of isothiocyanates, 3-isothiazolones, and other electrophilic derivatives to affinity label biopolymers has been described 13,35…”
Section: Resultsmentioning
confidence: 99%
“…Amide-linked fluorescent 1 and biotin-containing probes 2 and 3 of high A 3 AR affinity and selectivity were designed using a functionalized congener approach based on stepwise chain extension designed to preserve or enhance receptor affinity (Chart 1). 13…”
Section: Introductionmentioning
confidence: 99%
“…Uridine-5′-diphosphoglucuronic acid and its ethylenediamine adduct were suitable functionalized congeners (50) for coupling to several generations (G2.5–6) of dendrimers (both terminal carboxy and amino) to modulate potency of the intact conjugates. The observed biological activity of the dendrimer conjugates was clearly P2Y 14 receptor-dependent; the control dendrimers 4 and 5 lacking nucleotides were inactive.…”
Section: Discussionmentioning
confidence: 99%
“…Although only one fluorescent conjugate 16 showed high potency at the P2Y 6 R, this site on the nucleotide promises to be a general site for derivatization with bulky substituents, including other fluorophores and specialized reporter groups for receptor detection and characterization. 39 A molecular modeling study was carried out to explore the recognition of the agonist 16 in binding to the P2Y 6 R to highlight the key putative interactions between charged groups of a large fluorophore moiety and the outer regions of TM3 in the P2Y 6 R, which evidently enhance the potency of 16 . In conclusion, we have identified the N 4 -benzyloxy group as a structurally permissive region for synthesis of a family of functionalized congeners as fluorescent conjugates and other pharmacological probes for studying the P2Y 6 R. This will enable further drug discovery related to this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…A functionalized congener approach to ligand derivatization has been explored for a variety of GPCRs, leading to fluorescent probes, 18 affinity labels, cross-linking ligands, and specialized radioactive probes. 39 SAR analyses suggested that the steric constraints of the pharmacophoric binding site of the receptor likely could be circumvented by chain elongation through two specific sites in P2Y 6 R agonists. Thus, we introduced a 4-alkyloxyimino group in the nucleobase, and the terminal phosphate group was extended in γ-ester derivatives of UTP.…”
Section: Introductionmentioning
confidence: 99%